Drug Use and Social Change - Shiner, M. author. aut Link
XI, 238 p. 8 illus.
Keywords: This book locates the rise of illicit drug use within the historical development of late industrial society and challenges the prevailing view. Highlighting key areas of continuity and the on-going value of classic criminological theory, it is argued that recent trends do not constitute the radical departure that is often supposed.